Production of highly aligned microfiber bundles from polymethyl methacrylate via stable jet electrospinning for organic solid‐state lasers. Issue 4 (11th December 2021) - Christ, Henrik‐Alexander; Ang, Pen Yiao; Li, Fuzhao; Johannes, Hans‐Hermann; Kowalsky, Wolfgang; Menzel, Henning
Abstract: The fabrication of micron‐sized poly(methyl methacrylate) (PMMA) polymer optical fibers doped with rhodamine B as an organic dye is demonstrated. Highly aligned and defect‐free fibers are fabricated by using the stable jet electrospinning (SJES) method and systematically varying critical parameters such as solvent type and polymer concentration. At optimal conditions, for example, a polymer concentration of 35 wt% of PMMA in butanone, ribbon‐shaped fibers with a smooth surface and diameter of about 20 μm could be spun using SJES mode and deposited on a rotating drum as target in a highly aligned manner. Photoluminescence spectra of the doped fibers excited longitudinally and transversely with a laser show an excitation peak with full‐width‐at‐half‐maximum of only 5.05 nm and a low lasing threshold at a pump energy of 0.55 μJ, indicating that SJES could become a new source of amplified optics components or organic solid‐state fiber lasers. Abstract :